Construir el pueblo aprista: el diario La Tribuna en su primer año de vida - Bergel, Martín (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
This article offers a meticulous reconstruction of the La Tribuna newspaper in its first year of existence. From a perspective that addresses both its discursive and material aspects, and in dialogue with recent historiography on the press and printed culture in Latin America, this essay argues that the official newspaper of APRA played a crucial role in the popularization of the party as well as in the very construction of the notion of an «Aprista people» («pueblo aprista»).La Tribuna was a tool that organized and gave visibility to the life of the party. But its initial success was not merely due to the fact of having positioned itself in that role, but also to having effectively coupled itself with the process of the periodical press’s modernization in Peru.

Este artículo ofrece una reconstrucción minuciosa del diario aprista La Tribuna en su primer año de existencia. Desde un ángulo que atiende tanto a sus aspectos discursivos como materiales, y en diálogo con la historiografía reciente sobre la prensa periódica y la cultura impresa en América Latina, este ensayo argumenta que el vocero oficial del APRA fue un dispositivo crucial tanto en el proceso de popularización de este partido como en la propia construcción de la noción de un «pueblo aprista». La Tribuna fue un artefacto que organizó y visibilizó la vida partidaria. Pero su éxito inicial no tuvo que ver meramente con el hecho de haberse posicionado en ese rol, sino también con haberse acoplado eficazmente al proceso de modernización de la prensa periódica en el Perú.
Building an Aprista People: The Newspaper La Tribuna in Its First Year of Existence
Keywords: Prensa Periódica; Populismo; Aprismo; Intelectuales; Modernización Cultural; https://purl.org/pe-repo/ocde/ford#6.01.01